2016
DOI: 10.1097/md.0000000000003083
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Kidney Perfusion Measurements With Arterial Spin Labeling at 1.5 Tesla MRI Combined With Semiautomatic Segmentation for Differential Cortical and Medullary Assessment

Abstract: Magnetic resonance imaging with arterial spin labeling (ASL) is a noninvasive approach to measure organ perfusion. The purpose of this study was to evaluate the reproducibility of ASL kidney perfusion measurements with semiautomatic segmentation, which allows separate quantification of cortical and medullary perfusion.The right kidneys of 14 healthy volunteers were examined 6 times on 2 occasions (3 times at each occasion). There was a 10-minute pause between each examination and a 14-day interval between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“… 13 , 28 Although only a few studies evaluating ASL MRI measurements have been performed to date, the technique has been shown to be reproducible. 29 , 30 Furthermore, ASL MRI−derived perfusion estimates correlated well with para-aminohippuric acid measurements and were able to discriminate pharmacologic changes in renal plasma flow. 31 The comparison of the ASL technique with a microsphere method in an animal model has shown that cortical perfusion measured with ASL correlated with microspheres in the expected physiologic range.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“… 13 , 28 Although only a few studies evaluating ASL MRI measurements have been performed to date, the technique has been shown to be reproducible. 29 , 30 Furthermore, ASL MRI−derived perfusion estimates correlated well with para-aminohippuric acid measurements and were able to discriminate pharmacologic changes in renal plasma flow. 31 The comparison of the ASL technique with a microsphere method in an animal model has shown that cortical perfusion measured with ASL correlated with microspheres in the expected physiologic range.…”
Section: Discussionmentioning
confidence: 72%
“…A recent report suggests a high degree of reproducibility of renal ASL MRI when repeated after 2 weeks. 29 In this study, we used longer TI for patients, assuming slower circulation compared to that of controls. 13 , 34 Although this is not ideal, it should not unduly influence the estimated flow, as the quantitation takes TI in to account.…”
Section: Discussionmentioning
confidence: 99%
“…By subtracting labeled images (radiofrequency magnetic labeling) from control images (no labeling applied), perfusion maps can be quantified using a kinetic model (Buxton et al, 1998 ). Renal tissue perfusion assessed by ASL has been implemented in healthy (Karger et al, 2000 ; Martirosian et al, 2004 ; Boss et al, 2005 ; Kiefer et al, 2009 ; Gardener and Francis, 2010 ; Cutajar et al, 2012 , 2014 ; Park et al, 2013 ; Gillis et al, 2014 ; Tan et al, 2014 ; Hammon et al, 2016 ), transplanted (Artz et al, 2011a , b ; Niles et al, 2016 ) and diseased (Michaely et al, 2004 ; Boss et al, 2005 ; Fenchel et al, 2006 ; Ritt et al, 2010 ; Rossi et al, 2012 ; Dong et al, 2013 ; Heusch et al, 2013 ; Tan et al, 2014 ) kidneys.…”
Section: Methodsmentioning
confidence: 99%
“…A good repeatability of the perfusion measurements (reported as coefficient of variation, CV) was found over the cortex [29,32,33,34] (CV = 4-16%) and the whole kidney [33,34] (CV = 3-7%), while the data for the renal medulla are sparse [34]. A good correlation of the cortical renal blood flow (RBF) was found for ASL and DSC MRI [29,35] in healthy volunteers.…”
Section: Renal Asl Mri In Healthy Volunteersmentioning
confidence: 99%